Implementasi Peraturan Presiden Republik Indonesia Nomor 102 Tahun 2018 Tentang Tunjangan Kinerja Pegawai di Lingkungan Tentara Nasional Indonesia - Chairunnisa, Dwi Ayu; Irawanto, I; khariry, Mukhlan; Priono, Singgih (Administraus, 2024)
The purpose of this study is to determine how the implementation of the provision of performance allowances for soldiers in Koopssus TNI is in accordance with the provisions of TNI Commander Regulation Number 4 of 2012 concerning Administrative Guidelines for Providing Performance Allowances for Soldiers and Civil Servants in the TNI Environment. Meanwhile, the procedure for providing performance allowances for soldiers in Koopssus TNI is carried out through authorisation channels because the performance allowance budget has not been included in the TNI budget for personnel expenditure. In order for the provision of performance allowances to be carried out effectively and efficiently, the submission and distribution procedures must be clearly arranged to avoid errors and leakage of the performance allowance budget. Based on the results of the study, it can be concluded that the implementation of providing performance allowances for soldiers in the TNI Coopssus has been running well, this is in accordance with the exploration of implementation dimensions such as communication, resources, attitudes and bureaucratic structures towards informants, who state that the implementation of providing performance allowances in the TNI Coopssus has been running well. Keywords: Implementation, Performance Allowance, and Soldiers ABSTRAK Tujuan penelitian ini adalah untuk mengetahui bagaimana implementasi pemberian tunjangan kinerja bagi prajurit di Koopssus TNI sesuai dengan ketentuan Peraturan Panglima TNI Nomor 4 Tahun 2012 Tentang Petunjuk Adminstrasi Pemberian Tunjangan Kinerja bagi Prajurit dan PNS di Lingkungan TNI. Sedangkan prosedur pemberian tunjangan kinerja bagi prajurit di Koopssus TNI dilaksanakan melalui jalur otorisasi karena anggaran tunjangan kinerja tersebut belum masuk anggaran TNI untuk belanja pegawai. Agar pemberian tunjangan kinerja dapat dilaksanakan secara efektif dan efisien maka prosedur pengajuan dan penyalurannya harus diataur secara jelas untuk menghindari adanya kesalahan dan kebocoran anggaran tunjangan kinerja tersebut. Berdasarkan hasil penelitian dapat disimpulkan bahwa implementasi pemberian tunjangan kinerja bagi prajurit di Koopssus TNI telah berjalan dengan baik, hal ini sesuai dengan penelusuran dimensi-dimensi implementasi seperti komunikasi, sumber daya, sikap dan struktur birokrasi terhadap para informan, yang menyatakan bahwa implementasi pemberian tunjangan kinerja di Koopssus TNI telah berjalan dengan baik. Kata Kunci: Manajemen, Penaggulangan Bencana Daerah